G2019S LRRK2 enhances the neuronal transmission of tau in the mouse brain. (27th October 2017) - Nguyen, An Phu Tran; Daniel, Guillaume; Valdés, Pamela; Islam, Md Shariful; Schneider, Bernard L; Moore, Darren J
Abstract: Mutations in the leucine-rich repeat kinase 2 ( LRRK2 ) gene cause late-onset, autosomal dominant Parkinson's disease (PD). LRRK2 mutations typically give rise to Lewy pathology in the brains of PD subjects yet can induce tau-positive neuropathology in some cases. The pathological interaction between LRRK2 and tau remains poorly defined. To explore this interaction in vivo, we crossed a well-characterized human P301S-tau transgenic mouse model of tauopathy with human G2019S-LRRK2 transgenic mice or LRRK2 knockout (KO) mice. We find that endogenous or pathogenic LRRK2 expression has minimal effects on the steady-state levels, solubility and abnormal phosphorylation of human P301S-tau throughout the mouse brain. We next developed a new model of tauopathy by delivering AAV2/6 vectors expressing human P301S-tau to the hippocampal CA1 region of G2019S-LRRK2 transgenic or LRRK2 KO mice. P301S-tau expression induces hippocampal tau pathology and marked degeneration of CA1 pyramidal neurons in mice, however, this occurs independently of endogenous or pathogenic LRRK2 expression. We further developed new AAV2/6 vectors co-expressing human WT-tau and GFP to monitor the neuron-to-neuron transmission of tau within defined hippocampal neuronal circuits. While endogenous LRRK2 is not required for tau transmission, we find that G2019S-LRRK2 markedly enhances the neuron-to-neuron transmission of tau in mice. Our data suggest that mutant tau-induced neuropathology occurs independently of LRRK2 expression in two mouse models of tauopathy but identifies a novel pathogenic role for G2019S-LRRK2 in promoting the neuronal transmission of WT-tau protein. These findings may have important implications for understanding the development of tau neuropathology in LRRK2 -linked PD brains.